2021
DOI: 10.3390/nu13030993
|View full text |Cite
|
Sign up to set email alerts
|

Role of HO-1 against Saturated Fatty Acid-Induced Oxidative Stress in Hepatocytes

Abstract: Increased circulating levels of free fatty acids, especially saturated ones, are involved in disease progression in the non-alcoholic fatty liver. Although the mechanism of saturated fatty acid-induced toxicity in the liver is not fully understood, oxidative stress may be deeply involved. We examined the effect of increased palmitic acid, the most common saturated fatty acid in the blood, on the liver of BALB/c mice via tail vein injection with palmitate. After 24 h, among several anti-oxidative stress respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Decreased hepatic HO-1 expression was reported to improve oxidative stress in the liver and ameliorate the development of NAFLD. 40,41 Importantly, our findings showed that Britanin inhibited oxidative stress by downregulating the level of HO-1 expression. Moreover, the AMPK/SREBP1c pathway that is correlated with lipid metabolism was shown to participate in the Britanin-provided alleviation on NAFLD.…”
Section: ■ Discussionmentioning
confidence: 57%
“…Decreased hepatic HO-1 expression was reported to improve oxidative stress in the liver and ameliorate the development of NAFLD. 40,41 Importantly, our findings showed that Britanin inhibited oxidative stress by downregulating the level of HO-1 expression. Moreover, the AMPK/SREBP1c pathway that is correlated with lipid metabolism was shown to participate in the Britanin-provided alleviation on NAFLD.…”
Section: ■ Discussionmentioning
confidence: 57%
“…SFAs such as palmitic acid suppress autophagy in hepatocytes, decreasing the levels of Nrf2, inducing ferroptosis of hepatocytes 39,40 . In a similar manner, excess intake of dietary SFA may promote ferroptosis of melanocytes in patients with vitiligo.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Zeng et al demonstrated that increased levels of PA at the expense of OA are responsible for inflammasome and GSDMD activation, leading to pyroptosis-mediated cell death [ 12 ]. However, Akazawa and Nakao, as well as other groups, independently reported that high PA levels induce phospho-RIP-1-mediated necroptosis [ 10 , 18 , 19 ] with a promotion of mitochondrial ROS that allows the auto-phosphorylation of RIP-1 [ 20 , 21 ]. In addition, although several studies have demonstrated the toxicity of exosomes carrying PA, no studies have yet been conducted on the balance between PA and OA within the exosomes, and hence on their ratio, as the crucial player in the cell death event, rather than the individual exosome fatty level.…”
Section: Introductionmentioning
confidence: 99%